2021
DOI: 10.1186/s12883-021-02052-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and adherence to moderate intensity cardiovascular fitness training following stroke: a pilot randomized controlled trial

Abstract: Background Stroke is a leading cause of disability worldwide and the cardiovascular fitness levels of stroke survivors are diminished to an extent that impairs functioning and activities of daily living performance. While cardiovascular training seems an empirically appropriate intervention, the optimal dosage and intensity of cardiovascular training in stroke survivors remains unclear. The aim was to determine the safety and feasibility of moderate-intensity cardiovascular training following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…In a recent community-based exercise trial of ambulatory people post-stroke, participants struggled to achieve and sustain the prescribed dose of exercise. 53 Issues underlying this problem were not explored by the investigators but previously reported personal barriers to exercise post-stroke, including lack of motivation to exercise, health concerns (e.g., fatigue and depression), and motor impairments, may have been contributing factors. 54 The importance of exercise dose to exercise-related outcomes is well documented in older adults 55 (e.g., a robust dose–response relationship is often observed between intensity of aerobic exercise and HDL-C levels 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent community-based exercise trial of ambulatory people post-stroke, participants struggled to achieve and sustain the prescribed dose of exercise. 53 Issues underlying this problem were not explored by the investigators but previously reported personal barriers to exercise post-stroke, including lack of motivation to exercise, health concerns (e.g., fatigue and depression), and motor impairments, may have been contributing factors. 54 The importance of exercise dose to exercise-related outcomes is well documented in older adults 55 (e.g., a robust dose–response relationship is often observed between intensity of aerobic exercise and HDL-C levels 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In total, participants attended 1,675 (85%) of 1,980 planned treatment sessions and 197 (90%) of 220 planned testing sessions. 67 [62,72] 52 [47,57] 15 [8,22] 0.0002 Block 2 (sessions [13][14][15][16][17][18][19][20][21][22][23][24] 77 [72,82] 59 [54,64] 18 [11,26] <0.0001 Block 3 (sessions [25][26][27][28][29][30][31][32][33][34][35][36] 82 [77,87] 65 [59,70] 17 [10,25] <0.0001…”
Section: Recruitment and Retentionmentioning
confidence: 99%
“…[6][7][8] Studies also suggest that a more vigorous training intensity (>60% HRR vs 40-60% HRR) could augment outcomes, 9 but that a vigorous intensity can be difficult to achieve and sustain for many persons with stroke. [34][35][36] Thus, high-intensity interval training (HIT) has emerged as a promising strategy for post-stroke locomotor exercise. 37,38 This method involves bursts of fast walking alternated with recovery periods, and is designed to enable higher sustained intensities 39 at lower perceived exertion than high-intensity continuous exercise.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have found that moderate (40%-59% HRR) and high intensity (60%-84% HRR) aerobic exercise significantly improve exercise capacity, the low intensity (<40% HRR) is prescribed for most people with stroke. [ 12 ] The moderate- intensity fitness training safe but achievement of target duration and intensity was challenging for chronic stroke patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] The moderate- intensity fitness training safe but achievement of target duration and intensity was challenging for chronic stroke patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%